(untitled) (Journal of Pharmaceutical Negative Results, 2023)
David Mamet, an American playwright, film maker and author, introduces the ‘Student-Teacher’ (Huebert-Leibler 1988) relationship in many of his plays. ‘Oleanna (OL),’ produced in 1992, is one such play where the main theme is teacher-student relationship. By bringing in a conflict between the teacher, John, and the student, Carol, Mamet points out the drawback in American Education System that “subverts and distorts the people within it” (Sauer 2003). He portrays the teacher as a man of free thought, patience and knowledge. He also underlines the importance of imparting practical and application-oriented knowledge and also stresses the need for breaking the constraints of conventional educational system. As Brenda Murphy (2004) states the play derives its title from the Norwegian violinist Ole Bull and his wife Anna, who founded the Utopian Community Oleanna, which was named after the founders. Mamet wants to bring in a comparison between this community’s failure in their agricultural endeavor and the failure in the American education system and hence this title. This paper scrutinizes ‘Oleanna’ to underline the need for humanistic approach in the academia.